2019
DOI: 10.3390/antiox8110508
|View full text |Cite
|
Sign up to set email alerts
|

Protein Carbonylation in Patients with Myelodysplastic Syndrome: An Opportunity for Deferasirox Therapy

Abstract: Control of oxidative stress in the bone marrow (BM) is key for maintaining the interplay between self-renewal, proliferation, and differentiation of hematopoietic cells. Breakdown of this regulation can lead to diseases characterized by BM failure such as the myelodysplastic syndromes (MDS). To better understand the role of oxidative stress in MDS development, we compared protein carbonylation as an indicator of oxidative stress in the BM of patients with MDS and control subjects, and also patients with MDS un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Moreover, Hlaváčková et al identified 27 carbonylated proteins unique for MDS-RS, most of them related with the acute-phase inflammation process [40]. Consistent with these findings, an analysis of protein carbonylation in the BM of patients with MDS showed a high level of carbonylation both in myeloid series and in erythroid precursors in patients [44].…”
Section: Myelodysplastic Syndromesmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, Hlaváčková et al identified 27 carbonylated proteins unique for MDS-RS, most of them related with the acute-phase inflammation process [40]. Consistent with these findings, an analysis of protein carbonylation in the BM of patients with MDS showed a high level of carbonylation both in myeloid series and in erythroid precursors in patients [44].…”
Section: Myelodysplastic Syndromesmentioning
confidence: 73%
“…control group [44]. Analysis of the lipid peroxidation products MDA and nitrite revealed significantly higher levels in patients with MDS and IOL compared with peers without IOL and the control group, and both parameters positively correlated with the levels of ferritin [41] (Figure 3).…”
Section: Myelodysplastic Syndromesmentioning
confidence: 89%
See 1 more Smart Citation
“…Then, the measurement of protein carbonylation is performed using mass spectrophotometry, immunodetection with DNPH-specific antibodies, an ELISA assay, or immunohistochemistry. The semiquantitative detection of carbonyl content in individual proteins is assessed by one-or two-dimension electrophoresis, followed by western blot [185][186][187].…”
Section: Protein Carbonylation As An Aging Biomarkermentioning
confidence: 99%
“…Finally, Rodríguez-García et al [20] studied protein carbonylation in patients with myelodysplastic syndromes. These patients had increased protein carbonyls, but levels decreased after treatment with an iron chelator (deferasirox).…”
mentioning
confidence: 99%